Institute of Metals Division - Lattice Defects and the Solution of Nitrogen in a Deformed Ferritic Steel: Part II - Identification of Defect Sites and Influence of Composition - H. A. Wriedt; L. S. Darken (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
In a previous paper,1 an experimental study of nitrogen dissolved in a cold-rolled ad heat-treated, low-carbon steel at 300° to 450°C yielded the equilibrium solubility relations and the concentrations of the two types of deject sites involved. In this paper, the probable identities of the defects that absorb nitrogen are restricted from the available evidence to screw dislocatioms for B sites, and to either micro crack surfaces or edge In a previous paper.' we reported an experimental study of the excess nitrogen solubility in a low-carbon steel produced by a combination of plastic deformation and nonrecrystallizing heat treatment. The concentrations of the defect sites that absorb the excess nitrogen were measured in terms of their capacities for nitrogen. Also measured were the equilibria of nitrogen distribution among the sites. Several problems and questions arise from these measurements. We should like a physical identifi- dislocations for A sites. The concentrations of these defects in experimental steel specimens are estimated from the concentrations of defect sites. finally, the influence of chemical composition upon the nitrogen-trapping defects—the relative numbers generated in deformation, the relative numbers surviving as temperature is raised, the apparent numbers observed, and the distribution equilibria-is discussed. cation of the defects involved and of the two kinds of nitrogen-absorbing sites, called A and B types, upon those defects; the concentrations of the defects themselves could then be computed. We should also like to know how exclusively the findings apply to the "X steel" used in the experiments and to what extent they apply to cold-rolled steel given no subsequent treatment. By considering the data already given, together with results from a few specific tests which will be reported as they are invoked, we are able to eliminate some interpretations altogether and to secure an acceptable though limited interpretation from among the remaining possibilities.